2004
DOI: 10.1503/cmaj.1031597
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of a self-reported history of varicella infection in determining immunity in adults

Abstract: ResearchRecherche V aricella infection (chickenpox) is highly contagious 1 and is spread by respiratory droplets or direct contact. Varicella can occur in nonimmune adults, in whom severity of the infection increases with age, 2 often causing serious morbidity and loss of work time. In Canada, 70% of 53 reported deaths caused by varicella between 1987 and 1996 occurred in adolescents and adults.3 When acquired during pregnancy, varicella can cause significant maternal, perinatal and infant morbidity.3 After va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…On the other hand, the NPV of a negative history of varicella was 34.5% in adolescents and 8.3% in adults. These findings indicate that a negative history of varicella is not a reliable predictor of lack of immunity in adolescents and young adults, a finding consistent with other studies 35–40 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the NPV of a negative history of varicella was 34.5% in adolescents and 8.3% in adults. These findings indicate that a negative history of varicella is not a reliable predictor of lack of immunity in adolescents and young adults, a finding consistent with other studies 35–40 …”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate that a nega-tive history of varicella is not a reliable predictor of lack of immunity in adolescents and young adults, a finding consistent with other studies. [35][36][37][38][39][40] A presumptive varicella immunisation strategy for all adolescents with a negative history has been administrated in several European countries. 7,9,41 WHO also recommends that varicella vaccine may be offered to individual adolescents and adults without a history of varicella.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we thought that the hemorrhagic varicella infection at the age of 16 years (6) could be a sign of immunodeficiency. However, the patient did not have a history of chickenpox in the past (a reliable surrogate of a lack of seroimmunity (42,43)) and he developed the varicella secondary to his brother, who suffered a less severe case. Varicella secondary attack rate among susceptible household contacts is high and at higher age, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been undertaken to establish whether a self‐reported history of primary VZV infection is a reliable indicator of seropositivity 11,12 . Specific population groups that have been studied include health care workers, pregnant women and military personnel 11 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several studies have been undertaken to establish whether a self-reported history of primary VZV infection is a reliable indicator of seropositivity. 11,12 Specific population groups that have been studied include health care workers, pregnant women and military personnel. 11 We are unaware of any studies investigating the prevalence of VZV immunity and the predictive value of a self-reported history of VZV in a group of patients receiving systemic immunosuppressive therapies.…”
Section: Discussionmentioning
confidence: 99%